A crucial role for GW182 and the DCP1:DCP2 decapping complex in miRNA-mediated gene silencing. - Rehwinkel, J.; Behm-Ansmant, I.; Gatfield, D.; Izaurralde, E. (RNA (New York, N.Y.), 2005)
In eukaryotic cells degradation of bulk mRNA in the 5' to 3' direction requires the consecutive action of the decapping complex (consisting of DCP1 and DCP2) and the 5' to 3' exonuclease XRN1. These enzymes are found in discrete cytoplasmic foci known as P-bodies or GW-bodies (because of the accumulation of the GW182 antigen). Proteins acting in other post-transcriptional processes have also been localized to P-bodies. These include SMG5, SMG7, and UPF1, which function in nonsense-mediated mRNA decay (NMD), and the Argonaute proteins that are essential for RNA interference (RNAi) and the micro-RNA (miRNA) pathway. In addition, XRN1 is required for degradation of mRNAs targeted by NMD and RNAi. To investigate a possible interplay between P-bodies and these post-transcriptional processes we depleted P-body or essential pathway components from Drosophila cells and analyzed the effects of these depletions on the expression of reporter constructs, allowing us to monitor specifically NMD, RNAi, or miRNA function. We show that the RNA-binding protein GW182 and the DCP1:DCP2 decapping complex are required for miRNA-mediated gene silencing, uncovering a crucial role for P-body components in the miRNA pathway. Our analysis also revealed that inhibition of one pathway by depletion of its key effectors does not prevent the functioning of the other pathways, suggesting a lack of interdependence in Drosophila.